Does a high peritoneal cancer index lead to a worse prognosis of patients with advanced ovarian cancer?: a systematic review and meta-analysis based on the latest evidence - Wang, Siyu; Liu, Shaoxuan; Liu, Fangyuan; Guo, Ying; Han, Fengjuan (Frontiers in Oncology, 2024)
The newest clinical evidence suggests that the relationship between the peritoneal cancer index (PCI) and the postoperative prognosis of advanced ovarian cancer patients remains controversial, and there are no largesample and multicenter studies to clarify this matter. Therefore, in this paper, we used meta-analysis to systematically assess the postoperative prognostic value of PCI in subjects with advanced ovarian cancer to provide individualized treatment plans and thus improve the prognosis of patients.Methods: Literature on the correlation between PCI and the postoperative prognosis in subjects with advanced OC undergoing cytoreductive surgery (CRS) was searched in the Cochrane Library, Pubmed, Embase, and Web of Science from the database inception to April 20, 2023. The search was updated on February 28, 2024. We only included late-stage (FIGO stage: III-IV) patients who did not undergo neoadjuvant chemotherapy (NACT) or hyperthermic intraperitoneal chemotherapy (HIPEC). Afterwards, literature screening and data extraction were conducted using Endnote20 software. The literature quality was assessed using the Newcastle-Ottawa Scale (NOS).Lastly, statistical analysis was performed with STATA 15.0 software.Five studies with 774 patients were included. The result indicated that patients with high PCI had a worse prognosis than those with low PCI. The combined hazard ratio was 2.79 [95%CI: (2.04, 3.82), p<0.001] for overall survival (OS) in patients with high PCI. Further subgroup analysis by the FIGO staging revealed that in stage III [HR: 2.61, 95%CI: (2.00, 3.40), p<0.001] and stage 95%CI: (1.66, 4.36), p<0.001], a high PCI score was significantly associated with a worse prognosis. The PCI score had a greater impact on the OS of patients with higher stages. The combined hazard ratio was 1.89 [95%CI: (1.51, 2.36), p<0.001] for progressionfree survival (PFS) in patients with high PCI.Conclusion: PCI may be used as a postoperative prognosis indicator in patients with advanced OC on primary debulking surgery. High PCI indicates a worse prognosis. However, further research is warranted to confirm these findings.